Tourism Development in Pelaga Village (Case Study in Pelaga Village, Petang District, Badung Regency) - I Putu Gita Setyawan; Nyoman Diah Utari; Ida Ayu Putu Sri Wahyuni (Musamus Journal of Public Administration, 2024)
This research aims to determine internal and external efforts that can be made to develop sustainable tourism in Pelaga Village, Petang District, Badung Regency. This research method uses descriptive qualitative. This research was conducted in Pelaga Village by focusing on three service banjars, namely Kiadan Service Banjar, Pelaga Service Banjar, and Bukian Service Banjar. This research was conducted from April to August 2023. The data collection methods used were observation, interviews, focus group discussion (FGD), and library methods. Determining the informants was carried out using a purposive technique, taking representatives of farmers from three service villages in Pelaga Village and the Pelaga Village apparatus, totaling 10 people. The data analysis method used in this research is the SWOT matrix. The research results prove that the strategy that can be implemented to develop tourism with an agricultural platform in Pelaga Village, Petang District, Badung Regency is a Strengths-Opportunities strategy, namely increasing tourism with an agricultural platform and maintaining various tourist attractions and promotional strategies. The Strengths-Threats strategy can be tried using 2 methods, namely the strategy of preparing provisions related to tourist areas and providing counseling to the residents of Pelaga Village. Weaknesses- Opportunities The strategy that can be tried is the preparation of location tourism. Strategy Weaknesses - Threats that can be provided are providing mastery training and tourism insight to the residents of Pelaga Village.